2022
DOI: 10.1002/app.52505
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of co‐electrospun gelatin:TiO2/polycaprolactone:silk fibroin scaffolds for wound healing applications

Abstract: Electrospinning is a facile technique to create porous nanofiber scaffolds with a high capability of natural environment mimicking. Here, co‐electrospinning of gelatin:TiO2, polycaprolactone:silk fibroin (G:T/P:F) was investigated with the aim of wound healing. Polycaprolactone improved the mechanical properties and gelatin:TiO2 enhanced cellular interactions. Silk fibroin was extracted from the Bombyx mori silkworm and increased the cellular and mechanical properties of the designed scaffolds. The morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 71 publications
(111 reference statements)
0
6
0
Order By: Relevance
“…100,101 Consequently, TiO 2 NPs find extensive application in wound treatment. 94,[102][103][104][105][106] Recently, Golipour et al 94 developed wound healing dressings by co-electrospinning of gelatin:TiO 2 and polycaprolactone:silk fibroin (G:T/P:F) (Fig. 5k).…”
Section: Anti-bacterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…100,101 Consequently, TiO 2 NPs find extensive application in wound treatment. 94,[102][103][104][105][106] Recently, Golipour et al 94 developed wound healing dressings by co-electrospinning of gelatin:TiO 2 and polycaprolactone:silk fibroin (G:T/P:F) (Fig. 5k).…”
Section: Anti-bacterialsmentioning
confidence: 99%
“…(k) Co-electrospun gelatin:TiO 2 /PCL:silk fibroin scaffolds (G:T/P:F) for antisepsis; (l) the antibacterial activity of G/P:F and G:T/P:F scaffolds against S. aureus and E. coli. Reproduced with permission 94. Copyright 2022, Wiley Periodicals LLC.…”
mentioning
confidence: 99%
“…These findings suggested its effectiveness in skin tissue regeneration. [156] and c) SF nanofibers are coated on TiO 2 -NTs to regulate vancomycin release, antimicrobial characteristics, and improve bone integration. The plan illustrates the movement of vancomycin molecules across SF nanofibers.…”
Section: Wound Healing and Skin Regenerationmentioning
confidence: 99%
“…Antimicrobial examination showed that PEO/CS (AgNPs) nanofibers had 51.2 ± 3.2 mm and 47.2 ± 2.1 mm inhibition circle diameters against E. coli and S. aureus , respectively (Figure 11b). Golipour et al 184 developed electrospinning nanofiber scaffolds using a blend of GE, TiO 2 , PLCL, and SF for applications in skin tissue regeneration and wound healing. The study highlighted that the inclusion of SF and TiO 2 in the nanofiber scaffolds significantly enhanced the hydrophobicity of PLCL, leading to a decrease in the contact angle from 86.5° to 54.6°.…”
Section: Electrospinning Wound Dressing With Functional Substancementioning
confidence: 99%